Evaluation of Polycladia myrica mediated selenium nanoparticles (PoSeNPS) cytotoxicity against PC-3 cells and antiviral activity against HAV HM175 (Hepatitis A), HSV-2 (Herpes simplex II), and Adenovirus strain 2 - Touliabah, Hussein Elsayed; El-Sheekh, Mostafa Mohamed; Makhlof, Mofida Elsayed Mohmed (Frontiers in Marine Science, 2022)
In this work, the selenium nanoparticles produced by the brown seaweed Cystoseira myrica were confirmed using various characterization techniques, including UV-Vis spectrum, FTIR spectroscopy, XRD diffraction, TEM photography, SEM photography, EDX analysis, and Zeta-potential. The phycosynthesized nanoparticles exhibit antiviral activity (40.25 ±2.61, 8.64 ±0.82, and 17.39 ±1.45 %) against HAV-10, Adenovirus, and HSV-2, respectively. The human prostate PC-3 and normal mammalian cells from the African green monkey kidney (Vero) were used to test the effectiveness of the produced CsSeNPS as an anticancer agent. The IC50 values of the two cell types were 123.51 4.07 g/ml and 220.53 6.89 g/ml, respectively. The maximum inhibitory percent was 86.152.31 against PC-3 cells. At the same time, at a concentration of 125 g/ml, CsSeNPS recorded viability percent of 78.39 and 49.23 against Vero and PC-3 cells, respectively, indicating that there was no danger to Vero cells. As a green use of nanotechnology, CsSeNPS demonstrated effective antiviral and anticancer properties against tested viruses and cancer cells.